Experimental study on RC beams strengthened with CFRP rod panels. (15th October 2018) - Jawdhari, Akram; Peiris, Abheetha; Harik, Issam
Graphical abstract: Performance of RC beams strengthened with full-length and spliced CFRP laminate and CRP. Highlights: CFRP rod panels (CRPs) are experimentally evaluated for the retrofit of reinforced concrete beams. CRPs can be spliced together using a finger joint to create a continuous strengthening system. Capacity increase for CRP strengthened reinforced concrete beams ranged from 112% to 158% above the control beam. When compared to CFRP laminates, CRP strengthened reinforced concrete beams had a higher load carrying capacity. The proposed 150 mm finger joint is able to provide continuity between adjacent CFRP rod panels. Abstract: Externally bonded (EB) fiber reinforced polymer (FRP) laminates and fabrics have become a mainstream method for retrofitting and upgrading concrete structures. Nevertheless, when strengthening long-span members or members with limited access, labor, traffic, and equipment demands may hinder the use of continuous EB FRP. The use of carbon FRP (CFRP) rod panels is a recent application of FRP material intended to overcome the above limitations. CFRP rod panels are developed from small diameter rods and are made continuous by means of a finger joint. This study leveraged four-point bending tests to determine whether spliced CFRP rod panels can effectively serve as flexural reinforcement for concrete members. Testing included a control beam and beams strengthened with the following FRP reinforcement layouts: (1) continuous rod panel, (2) spliced panel (two half-length panels with a 150 mm finger joint), (3) spliced panel anchored at ends with CFRP fabric, (4) continuous CFRP laminate, and (5) lap-spliced CFRP laminate system. Beams bonded with either continuous or spliced rod panels failed by concrete cover separation. The beam with spliced and anchored rod panel failed by intermediate crack-induced debonding of the panel. No local debonding or other signs of distress were observed at the finger joint for the two beams strengthened by spliced rod panels. For beams bonded with continuous and lap-spliced CFRP laminates, the failure was by laminate debonding. Compared to a control specimen, the maximum load increase of the strengthened beams was as follows: 112% for the continuous rod panel; 106% for spliced rod panel; 158% for the spliced/anchored rod panel; 49% for continuous laminate; and 31.8% for lap-spliced laminate.